The relationship between guilt feelings, conflicts with staff and satisfaction with care in relatives of nursing home residents with dementia: A longitudinal analysis. (January 2022) - Gallego-Alberto, Laura; Smaling, Hanneke JA; Francke, Anneke L; van de Brug, Tim; van der Steen, Jenny T; Joling, Karlijn J
Introduction: Family caregivers often experience guilt after nursing home placement. The aim of the present study was to describe family caregivers' guilt over time and assess the impact of conflicts with staff and satisfaction with care on guilt. Method: Data of 222 family caregivers at three assessments during one-year follow-up were used. In addition to caregivers' guilt and the variables conflicts with staff and satisfaction with the care, potential confounders were measured: sociodemographic data, clinical characteristics of the person with dementia, and caregiver burden. Linear mixed model analyses were performed to examine the longitudinal relationships between variables. Results: Guilt remained stable over time. Unadjusted models showed that conflicts with staff were positively associated with guilt ( β = 0.11; p < 0.001; 95% CI: 0.06 to 0.16) and satisfaction with care showed a negative association with guilt ( β = −0.10; p < 0.05; 95% CI: −0.18 to −0.01). After adjusting for the confounders, only the positive association of guilt with conflicts with staff was similar as in the unadjusted analysis ( β = 0.11; p < 0.001; 95% CI: 0.05 to 0.16), whereas satisfaction with care was not significantly associated with guilt in the adjusted analyses ( β = −0.07; p = 0.10; 95% CI: −0.16 to 0.01). Discussion: More conflicts with staff are associated with stronger guilt feelings. Guilt feelings are experienced by caregivers even after the admission of the person with dementia, and they remain stable over time. Further studies should focus on how to address guilt in family caregivers of people with dementia living in nursing homes.